2002
DOI: 10.1042/bj3640157
|View full text |Cite
|
Sign up to set email alerts
|

Novel disease-causing mutations in the dihydropyrimidine dehydrogenase gene interpreted by analysis of the three-dimensional protein structure

Abstract: Dihydropyrimidine dehydrogenase (DPD) deficiency is an autosomal recessive disease characterized by thymine-uraciluria in homozygous deficient patients. Cancer patients with a partial deficiency of DPD are at risk of developing severe life-threatening toxicities after the administration of 5-fluorouracil. Thus, identification of novel disease-causing mutations is of the utmost importance to allow screening of patients at risk. In eight patients presenting with a complete DPD deficiency, a considerable variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 24 publications
5
73
0
Order By: Relevance
“…Because they have not necessarily correlated with phenotypic changes (e.g., differences in DPD enzyme activity, 5-FU pharmacokinetics and pharmacodynamics) (Collie-Duguid et al 2000;Johnson et al 2002;Zhu et al 2004;Seck et al 2005;Ridge et al 1998aRidge et al , 1998bHsiao et al 2004), all of these variations are generally accepted as common polymorphisms that result in unaltered function. Consistent with this, van Kuilenburg et al (2002) suggested that the Fig. 4 The combinations of block haplotypes in Japanese.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Because they have not necessarily correlated with phenotypic changes (e.g., differences in DPD enzyme activity, 5-FU pharmacokinetics and pharmacodynamics) (Collie-Duguid et al 2000;Johnson et al 2002;Zhu et al 2004;Seck et al 2005;Ridge et al 1998aRidge et al , 1998bHsiao et al 2004), all of these variations are generally accepted as common polymorphisms that result in unaltered function. Consistent with this, van Kuilenburg et al (2002) suggested that the Fig. 4 The combinations of block haplotypes in Japanese.…”
Section: Discussionsupporting
confidence: 60%
“…We also considered the locations of the residues in a three-dimensional (3D) framework provided by the crystal structures of pig DPD, which have recently been determined in complexes with NADPH and substrate (5-FU) (Dobritzsch et al 2001) or inhibitors (Dobritzsch et al 2002). The amino acid sequences of pig and human DPD are 93% identical (Mattison et al 2002), and the substituted residues and their neighboring residues are conserved between both enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…its influence on enzymatic activity. Using the new homology model with the amino acid exchange C29R, we can support the assumption of Kuilenburg et al, that there is no structure-based evidence for a substantially altered enzymatic activity due to the C29R mutation (Van Kuilenburg et al, 2002b). The impact of M166V, S534N and I543V on the activity of the enzyme is yet unclear.…”
Section: Crystal Structure Analysis Of Dpd Proteinsupporting
confidence: 58%
“…This patient harbored the quadruple mutant DPD protein with additional C29R and I543V exchanges. Although no evidence of an impairment of the enzymatic function due to the latter amino acid substitutions was obtained by the structural analysis (see also van Kuilenburg et al, 2002b), an accumulating impact of the four missense mutations C29R, M166V, S534N and I543V on destabilization of the dimeric protein complex cannot be ruled out. In this context it should also be noted that a recombinantly expressed DPD protein carrying the C29R mutation did not possess any residual activity in Escherichia coli (Vreken et al 1997).…”
Section: Discussionmentioning
confidence: 98%